Grounds for agreement : evaluating responses of Northern Territory governments to the Aboriginal Land Rights (Northern Territory) Act 1976 - Fletcher, Christine, 1944-; Australian National University. North Australia Research Unit. (Darwin : North Australia Research Unit, National Centre for Development Studies, Research School of Pacific and Asian Studies, Australian National University, 1998)
Evaluates the Northern Territory government response to the Aboriginal Land Rights (Northern Territory) Act 1976; expenditure needs; role played by Commonwealth financial assistance grants; relationship between the government and the Land Councils; costs associated with government legal challenges to Aboriginal land claims - public expenditure, delivery of essential services to Aboriginal communities, costs due to past government inaction.
Bibliography: 25-28 p.
Keywords: Australia; Aboriginal Australians -- Land tenure -- Northern Territory; Land rights - Claims, disputes, hearings; Government policy - State and territory - Northern Territory; Finance - Budgets; Government policy - Commonwealth; Law - Land - State and Territory - Northern Territory; Councils - Land Councils; Northern Territory (NT)